HORMONE THERAPY WITH USAGE OF AGONISTS AND ANTAGONISTS OF LUTEINIZING HORMONE RELEASING HORMONE IN PATIENTS WITH PROSTATE CANCER - K. M. Nyushko; A. A. Krasheninnikov; M. P. Golovaschenko; A. D. Kaprin (Исследования и практика в медицине)
Prostate cancer (PC) is one of the most actual problems of modern oncourology. Hormone therapy (HT) using medical castration is the main method of treatment of patients with metastatic PC. HT with usage of the new class of drugs that block the receptors for luteinizing hormone releasing hormone (LHRH) is a promising and effective method of castration therapy that has a number of significant advantages over the use of analogues LHRH. This article presents areview of studies that compared the effectiveness and side effects of HT using antagonists and analogues LHRH.